Occupational safety and health in the emergency services - Angle, James (Burlington, MA Jones & Bartlett Learning, 2022)
"Designed for use within courses based on the Fire and Emergency Services Higher Education (FESHE) Occupational Safety and Health for Emergency Services model curriculum, Occupational Safety and Health in the Emergency Services, Fourth Edition provides a comprehensive overview of the many components of occupational safety and health for the emergency services. This textbook provides a historical look at industrial safety and health and how history has impacted the emergency services by providing a safer work environment that reduces first responder deaths and injuries. Occupational Safety and Health in the Emergency Services features a laser-like focus on fire fighter health and safety and details how to stay safe and healthy in a high-risk environment and includes: Thorough coverage of the "16 Fire Fighter Life safety Initiatives" with emphasis on the positive impact these Initiatives can have when implemented. Case studies, review and discussion questions, and additional resources for each chapter. Discussion on the latest research from Underwriters Laboratories (UL) and National Institute of Standards and Technology (NIST)"--
Includes index.
Keywords: Emergency medical personnel -- Health and hygiene; Emergency medical personnel -- Safety measures; Fire fighters -- Health and hygiene; Fire fighters -- Safety measures